A new species of Dasylabris Radoszkowski, 1885 (Hymenoptera: Mutillidae) from India - Terine, Joshua B.; Kumar, Girish P.; Adithya, Yogesh B. (Zootaxa, 2023)
We report the complete mitochondrial genome of the Cretan bush cricket Poecilimon cretensis. The mitogenome consists of 13 protein-coding regions, 22 tRNAs, two rRNAs, and one control region. The length of mitogenome in P. cretensis varies between15477 and 15631 bp, mainly due to variability in control region. The start and stop codons of protein coding genes exhibit the general pattern in Phaneropterinae. Phylogenetic tree constructed with the mitogenome obtained during this study and 12 mitogenomes of Phaneropterinae downloaded from GenBank, placed P. cretensis in Barbitistini as sister group to Poecilimon luschani. Data indicate that the gene overlapping pattern exhibit strong phylogenetic signals.